Bi-atrial fibrosis detected using three-dimensional late gadolinium enhancement magnetic resonance imaging in a patient with cardiac sarcoidosis. Issue 5 (16th May 2018) - Spence, Stewart; Pena, Elena; Thornhill, Rebecca E; Nery, Pablo B; Birnie, David H
Abstract: Presented is the case of a 62-year old male with a history of sarcoidosis and sinus node dysfunction, who underwent late gadolinium enhancement magnetic resonance imaging, which demonstrated left ventricular hyperenhancement and bi-atrial fibrosis.